2002
DOI: 10.1097/00129234-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Measurement

Abstract: Healthcare consumers are demanding excellence in care and services from care providers, and payors are following in their expectations. Demonstration of quality outcomes and consumer satisfaction with services are now a priority and the primary competitive edge in healthcare. Hospitals and healthcare systems that invest in programs to determine how patients evaluate their experiences will have valuable information to make transformational changes in care delivery and services. The purpose of this article is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…Our results, as well as those of other studies [25][26][27], showed that the CSQ-3 items have a good internal reliability for measuring general satisfaction of parents. A common phenomenon of the surveys evaluating satisfaction, including ours, is to produce highly skewed distribution of the satisfaction towards higher levels of satisfaction [14,16,17,25]. This ceiling effect could have occurred in our study because the range of the four-point Likert scale used with the CSQ-3 was probably not broad enough to detect satisfaction variations among individuals with high levels of satisfaction [29].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results, as well as those of other studies [25][26][27], showed that the CSQ-3 items have a good internal reliability for measuring general satisfaction of parents. A common phenomenon of the surveys evaluating satisfaction, including ours, is to produce highly skewed distribution of the satisfaction towards higher levels of satisfaction [14,16,17,25]. This ceiling effect could have occurred in our study because the range of the four-point Likert scale used with the CSQ-3 was probably not broad enough to detect satisfaction variations among individuals with high levels of satisfaction [29].…”
Section: Discussionmentioning
confidence: 88%
“…Parent satisfaction with care is a measure of quality of care [12][13][14]. Satisfaction refers to the degree to which parents perceive that the services meet their needs and those of their child.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 It is important for parents to feel that they can communicate with the doctors and neonatal nurse practitioners (NNPs) in the NICU, 3 so that they can understand their baby's condition, participate in medical decision making and care for their baby appropriately. The stress, technology and dynamic intensity of the NICU environment can be barriers to communication between parents and medical providers.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are referred to as “constructs,” and their relationship is complex. 7, 8 Regardless, satisfaction is an important metric to target and directly effects a hospital’s bottom line. Patients may perceive the quality of their care based on their interaction with staff, their environment, continuity of care, communication with their physicians, and wait times, as well as many non-modifiable factors such as socioeconomic status, race, sex, etc.…”
Section: Discussionmentioning
confidence: 99%